B Value Variation Using Adc Mapping Technique With Diffusion Weighted Imaging Sequence to Distinguish Musculoskeletal Tumor Malignancy - Celine Catharina Rosar, Celine
ABSTRACT Introduction: Diffusion Weighted Imaging (DWI) is a sequence which owned by MRI that used the diffusion of water molecules called Brownian motion. Accordingly, DWI is a noninvasive approach for investigating tumor histological content. The yield of ADC value influenced by b value parameter. The aim of this research is to oppose the diagnostic performance of DWI sequence by using b value of 800 s/mm2 and 1000 s/mm2 respectively at MRI 1,5 T for the indentification of clinically musculoskeletal tumors using ADC mapping as a quantitative marking tool. Methods: DWI has been done on 15 patients with soft tissue tumors and used two different b value of 800 s/mm2 and 1000 s/mm2 respectively. Then, it was placed ROI in a restricted area during post processing to produce ADC Mapping values. ROI measurement are taken to the solid section of the tumors. Results: ADC value when using b value of 800 s/mm2 is higher than using b value of 1000 s/mm2 (p < 0,05). The mean value of ADC on the use of b value of 800 s/mm2 is 2.50±0,04x10-3 while on the use of b value of 1000 s/mm2 is 1.96±0,03x10-3. Furthermore, b value in benign tumors group are higher than in malignant tumors group. Conclusion: ADC value was totally different when using different parameter of b value. And the best b value to distinguish malignant and benign musculoskeletal tumors is using b value of 800 s/mm2 .